Quality Assurance in Higher Education Didactics (KULT_online, 2009)
Förderung von Kompetenzen in der Hochschullehre is a volume of collected papers edited by Birgit Hawelka, Marianne Hammerl, and Hans Gruber that documents advanced training for university educators at Bavarian universities that have developed a joint curriculum for Didactics. The curriculum is meant to nurture competencies and increase the career satisfaction of university educators. The syllabus covers all central topics directly affecting the duties of teaching, advising, and exam administration. The papers are rooted in theory, but also provide a variety of suggestions, tips, and practical applications. This volume will therefore specifically appeal to university educators who wish to augment their professional competencies and broaden their instructional repertoires.